29‐3: Highly Versatile and Stable Photoalignment Process for AMLCDs. Issue 1 (30th May 2018) - McGinty, Colin; Wang, Junren; Finnemeyer, Valerie; Reich, Robert; Clark, Harry; Berry, Shaun; Bos, Philip
Abstract : A simple process for a reactive mesogen (RM) alignment layer is demonstrated with potential wide spread application in liquid crystal devices. A low concentration (0.3% wt) of RM dissolved in a liquid crystal is aligned by an azodye layer. After polymerization of the RM, the azodye is "bleached" to remove its visible absorption. The result is a versatile, low cost, stable alignment layer that is practical for AMLCDs.